Between aesthetics, ethics and politics: semiotic reflections on dis-taste - Stano, Simona (E|C, 2020)
Always central to the selection and consumption of food, sight has come to almost completely substitute taste: we no longer simply eat food, but above all we represent it, we imagine it, we share photographs of it. In this context, tasty foods play a fundamental role, according to the markedly performative logic of the so-called food porn, and increasingly also those that are dis-tasty, which, through particular enunciative strategies and rhetorical devices, manage to distance themselves from the physiological and evolutionary vision that linked in an indissoluble way their refusal to protect health and psycho-physical well-being to become themselves "appetizing". Through the semiotic analysis of some particularly significant case studies and the forms of textuality connected to them, this paper identifies and describes the main aesthetic and food policies promoted by this phenomenon, following the interesting reflection on the gustatory experience at the intersection between the aesthetic and phenomenological dimensions, on the one hand, and the socio-cultural universe, on the other.